Mass psychogenic illness following HPV immunization in Carmen de Bolivar, Colombia (2014): more uncertainty is required - Alvaro J. Idrovo; Gabriel D. Pinilla-Monsalve; Edgar F. Manrique-Hernández (Taylor & Francis Group, 2019)
The interesting article by Simas et. al. describes an outbreak case with over 600 individuals who exhibited neurological symptoms and which occurred in a town located at the northern region of Colombia in 2014. The community associated this event to the second-dose vaccination campaign against the Human Papillomavirus (HPV) and scientists defined it as a mass psychogenic illness. Unfortunately, the authors did not include in their article important findings related to a case-control study (with n = 137 and n = 437, respectively), conducted by the Colombian government. After inquiring "have you ever received vaccination against human papillomavirus?", a significant association with the vaccine was identified (adjusted OR: 10.8, 95% CI: 1.4-80.2).